THE EFFECT OF INTEREST RATE AND INFLATION ON THE GROWTH OF MUDHARABAH DEPOSITS AT BANK SUMUT SYARIAH MEDAN 2020-2024 - Dimas Akbar Nugroho; Juliana Nasution; Tuti Anggraini (Islamic Economic Law Study Program, Faculty of Sharia Sultan Aji Muhammad Idris Samarinda Islamic State University, 2026)
The growth of Islamic banking in Indonesia continues to expand alongside increasing public interest in a banking system that adheres to sharia principles, especially one that is free from usury (riba). Among its fund-collection instruments is the mudharabah deposit, namely a placement of funds based on a mudharabah contract that operates through a profit-sharing mechanism. This study examines the macroeconomic determinants of Islamic banking performance by analyzing the effects of the central bank interest rate (BI Rate) and the inflation rate on the growth of mudharabah (profit-sharing) savings deposits at Bank Sumut Syariah Medan. This research examines the influence of the interest rate and inflation on the volume of mudharabah deposits at Bank Sumut Syariah. The study applies an associative quantitative approach utilizing monthly secondary data covering the 2020–2024 period, sourced from the financial statements of Bank Sumut Syariah, Bank Indonesia, and the Central Statistics Agency (BPS). The data were processed through multiple linear regression with the aid of SPSS 22. The findings reveal that, simultaneously, the interest rate and inflation exert a significant effect on mudharabah deposits. On a partial basis, the interest rate demonstrates a significant positive effect, while inflation shows no significant effect. These results suggest that depositors' choices to allocate their funds into mudharabah deposits remain driven by a profit-oriented motive, which aligns with the displaced commercial risk encountered by Islamic banks operating within a dual banking system. This study implies that Islamic banks must dynamically adjust their profit-sharing ratios (nisbah) to remain competitive against conventional interest rate shifts, as regional depositors act as rational economic agents sensitive to inflation and market alternatives. Furthermore, monetary authorities must consider these dual-banking spillover effects to safeguard Islamic liquidity stability.